Health Risk Assessment of Phthalates in Children’s Toys - Ophithakorn, Thiwari; Phoungthong, Khamphe (Burapha Science Journal, 2026)
The amounts of phthalates impurities in children’s toys age 0 - 3 years in Hat Yai Municipality, Hat Yai District, Songkhla Province were explored. Three types of toys were investigated, including 1) pacifiers 2) teethers and 3) general toys (play with mouth). Forty samples were surveyed and collected during the period from August to December 2018. The phthalates from the samples were extracted by sonication method with tetrahydrofuran for 1 hour, and their amounts were measured with the Gas Chromatograph-Tandem Mass Spectrophotometer (GC-MS / MS). The contamination of DBP was detected in the range of 0.01 - 20 ng / mL (38% of samples) and DEHP was detected in the range of 500 - 1,000 ng / mL (48% of samples). Risk assessment of DBP and DEHP exposure in case of ingestion in children 1) between the ages of 3 months to less than 12 months 2) between the ages of 12 months to less than 24 months and 3) between the age of 24 months to less than 36 months and divided by male child group and female child group. Result of this study found that Hazard quotient and Hazard index assessed are less than 1 in all types of toys and less than 1 in all age groups and gender and still at a level that is not harmful to health. In addition to other groups of potentially harmful phthalates was detected, including Dimethyl phthalate (DMP) and Diethyl phthalate (DEP), therefore the relevant agencies should encourage to consider the control of dangers in children's toys without phthalates for the quality of life of Thai children in the future.